2017
DOI: 10.1111/jeb.13197
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and social brood effects on personality in juvenile and adult life‐history stages in a wild passerine

Abstract: How has evolution led to the variation in behavioural phenotypes (personalities) in a population? Knowledge of whether personality is heritable, and to what degree it is influenced by the social environment, is crucial to understanding its evolutionary significance, yet few estimates are available from natural populations. We tracked three behavioural traits during different life-history stages in a pedigreed population of wild house sparrows. Using a quantitative genetic approach, we demonstrated heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Previous studies on animal personality have primarily focused on the shy–bold continuum, which mainly quantifies behaviours based on an individual's willingness to take risks (Abbey‐Lee & Dingemanse, 2019; Dingemanse et al, 2004; Dingemanse & Réale, 2004; Smith & Blumstein, 2007). This research has shown that these personality types have a heritable component (Dochtermann & Royauté, 2019; Montiglio et al., 2013; van Oers et al., 2004; Winney et al., 2018). Different animal personality types have associated advantages and disadvantages, such as predator avoidance, access to social information, disease transmission and survival probability (Abbey‐Lee & Dingemanse, 2019; Moiron et al, 2020; Wilson et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on animal personality have primarily focused on the shy–bold continuum, which mainly quantifies behaviours based on an individual's willingness to take risks (Abbey‐Lee & Dingemanse, 2019; Dingemanse et al, 2004; Dingemanse & Réale, 2004; Smith & Blumstein, 2007). This research has shown that these personality types have a heritable component (Dochtermann & Royauté, 2019; Montiglio et al., 2013; van Oers et al., 2004; Winney et al., 2018). Different animal personality types have associated advantages and disadvantages, such as predator avoidance, access to social information, disease transmission and survival probability (Abbey‐Lee & Dingemanse, 2019; Moiron et al, 2020; Wilson et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although heritability and genetic correlations of animal “personality” traits (for instance exploration, activity, aggression and docility) have attracted a lot of attention recently (yellow‐bellied marmots, Petelle et al., ; red squirrels, Taylor et al., ; house sparrows, Winney et al., ), studies investigating genetic correlations between social (including cooperative) behaviours are lacking thus far. The present study addresses this by investigating the genetic variation and covariation of social behaviours in the cooperatively breeding cichlid fish Neolamprologus pulcher .…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the interactive nature of the social domain, an individual's social behavioural phenotype may be influenced by the behaviour of their social partners (Adams, Robinson, Mannarelli, & Hatchwell, 2015;Kasper, Kölliker, et al, 2017;Kasper, Vierbuchen, et al, 2017). Most studies investigate behavioural traits on a purely phenotypic level (but see Taylor et al, 2012;Petelle, Martin, & Blumstein, 2015;Winney et al, 2017;Kölliker, Brinkhof, Heeb, Fitze, & Richner, 2000;Kasper, Kölliker, et al, 2017), assuming that phenotypic patterns of (co)variance truthfully reflect genotypic patterns (Cheverud, 1988;Dochtermann, 2011). However, by assuming that phenotypic patterns reliably predict genetic patterns (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional traits of interest in eco‐evolutionary studies were typically morphological or life‐history traits; however, considerable attention is currently being paid to questions regarding within‐population variation in behavioral traits (Dingemanse, Kazem, Réale, & Wright, ; Réale, Reader, Sol, McDougall, & Dingemanse, ; Sih, Bell, Johnson, & Ziemba, ; Wolf & Weissing, ) Existing work on quantitative genetics of behavior suggests that behavioral traits are, on average, as heritable as life‐history traits and are subject to varying degrees of selection (Boake, ; Mousseau & Roff, ; Stirling et al, ). Earlier research tended to focus first on mating and sexually selected behaviors (Boake, ), but more studies have recently tested for heritability of behaviors, such as exploration, boldness, and activity, that can systematically lead to differences in how individuals interact with their environment (Ariyomo, Carter, & Watt, ; Bize, Diaz, & Lindström, ; Brommer & Kluen, ; Dingemanse, Both, Drent, Oers, & Noordwijk, ; Niemelä, Dingemanse, Alioravainen, Vainikka, & Kortet, ; van Oers, Drent, Goede, & Noordwijk, ; van Oers & Sinn, ; Patrick, Charmantier, & Weimerskirch, ; Réale, Gallant, Leblanc, & Festa‐Bianchet, ; Sinn, Apiolaza, & Moltschaniwskyj, ; Winney et al, ). Heritability estimates from these studies have been variable, with behaviors not uncommonly having low values or confidence intervals overlapping zero.…”
Section: Introductionmentioning
confidence: 99%
“…Significant areas of study include identifying the relative importance of genetic and environmental influences on the expression of phenotypes (Falconer & Mackay, 1996;Lynch & Walsh, 1998;Roff, 1997), quantifying the extent to which traits respond to developmental cues (Pigliucci, 2005;West-Eberhard, 2003), and measuring the link between fitness and genetic variation (Mousseau & Roff, 1987;Price & Schluter, 1991;Stirling, Réale, & Roff, 2002). Traditional traits of interest in eco-evolutionary studies were typically morphological Niemelä, Dingemanse, Alioravainen, Vainikka, & Kortet, 2013;van Oers, Drent, Goede, & Noordwijk, 2004;van Oers & Sinn, 2011;Patrick, Charmantier, & Weimerskirch, 2013;Réale, Gallant, Leblanc, & Festa-Bianchet, 2000;Sinn, Apiolaza, & Moltschaniwskyj, 2006;Winney et al, 2018). Heritability estimates from these studies have been variable, with behaviors not uncommonly having low values or confidence intervals overlapping zero.…”
Section: Introductionmentioning
confidence: 99%